Clinical and economic impact of changing reimbursement criteria for statin treatment among patients with type 2 diabetes mellitus in South Korea - Kim, Siin; Choi, Kyungseon; Kim, Ji-yool; Suh, Hae Sun (Frontiers in Pharmacology, 2022)
Aim: Patients with type 2 diabetes mellitus (T2DM) in South Korea can be reimbursed for statins if they have a low-density lipoprotein cholesterol (LDL-C) level of ≥100 mg/dL. We aimed to explore the clinical and economic benefit received by T2DM patients when easing the current criteria for statin treatment by lowering the LDL-C threshold from 100 mg/dL to 70 mg/dL. Methods: We used a static course model with a 5-year period to compare the following two scenarios in T2DM patients with no history of cardiovascular (CV) events: the current criteria covering LDL-C ≥100 mg/dL and the revised criteria covering LDL-C ≥70 mg/dL. The number of target patients was estimated based on previous Korean studies on patients with T2DM. The current mix of treatments used for T2DM and costs involving CV events were estimated using the National Health Insurance Service – National Health Screening Cohort database. The baseline CV event rates and case fatality were estimated using NHIS Customized database, including 50% patients who were prescribed atorvastatin and 100% who were not prescribed statins between 2009 and 2012 among patients with T2DM in the entire Korean population. After propensity score matching, patients with T2DM not prescribed statins were followed up until 2018 to estimate the incidence rates of coronary heart disease (CHD) and stroke. The efficacy of atorvastatin for the primary prevention of CV events in patients with T2DM was derived from a pivotal clinical trial. The outcome measures were the number of CV events prevented after the change in criteria and the consequent cost savings. Results: In South Korea, the current and revised criteria covered 2,434,379 and 3,446,149 patients with T2DM, respectively. The change in criteria resulted in the prevention of 726 CV events and cost savings of US dollars (USD) 5.5 million at the national level and USD 0.0089 per member per month in the fifth year. Conclusions: Easing the reimbursement criteria for statin treatment among patients with T2DM was associated with a reduction in CV events and their related costs; therefore, changing the reimbursement criteria is worth further consideration to mitigate the burden of CV disease.